Islamic perspectives on the legality of marital rape in the framework of maqasid al-shariah - Mohd Nasri, Mohd Mukhlis; Awang Hamat, Mohd Afandi (The Islamic Quarterly Journal of Islamic Perspectives, 2018)
The term “marital rape” is commonly used by politicians, human rights activists, and feminists to refer to a husband who forces sexual intercourse upon his wife without her consent. Since some NGOs have reported to the United Nations about the elimination of discrimination against women in Malaysia, they suggested to the government that marital rape must be considered as an offence in its penal code. Thus, this issue has become quite controversial amongst Muslims in Malaysia given that it is widely believed in Islamic law that rape cannot occur inside the institution of marriage. This paper, therefore, aims to clarify the concept of marital rape in Islam focusing primarily on the husband’s and wife’s rights to sexual intercourse within the framework of the maqāṣid al-sharī’ah. The information in this article has been obtained through secondary references, traditional literature on Islamic jurisprudence, exegesis of the Qur’an and hadith, as well as library research in order to attain its objectives. Based on the research findings, this study elucidates the spouses’ sexual rights from an Islamic perspective in accordance with the framework of the maqāṣid al-sharī’ah.